PRAKTIK DROPSHIPPING DALAM PERSPEKTIF HUKUM DAGANG DAN HUKUM POSITIF DI INDONESIA - Enjum Jumhana; Nurul Intan Sari; Ina Widiana Chandra; Khumairoh Cahya Azhari; Azzahra Putri Larasati; Ferdy Hendriansyah; Aula Ahkam (TAHKIM, 2026)
The development of digital commerce has given rise to various new business models, one of which is the dropshipping system. This model allows business actors to sell goods without owning or physically storing inventory, as the products are shipped directly from suppliers to consumers. Despite its efficiency and accessibility, dropshipping raises several legal issues, particularly concerning transaction validity, legal certainty, and consumer protection. This study examines the practice of dropshipping from the perspective of commercial law and positive law in Indonesia and analyzes its normative implications for business liability and consumer protection. This research employs a normative legal research method using statutory, conceptual, and limited comparative approaches. The legal materials analyzed consist of trade and consumer protection regulations, as well as legal doctrines and scholarly opinions. Data analysis is conducted qualitatively through a normative-prescriptive approach. The findings indicate that dropshipping practices can be considered legally valid sale and purchase agreements provided they fulfill the elements of consent and good faith. However, the absence of specific legal regulations governing dropshipping in Indonesian positive law creates normative gaps and potential legal uncertainty. Legally, the dropshipper is positioned as a business actor who bears direct responsibility toward consumers, regardless of the supplier’s role. This study concludes that regulatory reinforcement and adaptive legal policies are necessary to ensure legal certainty and effective consumer protection in dropshipping practices within Indonesia’s digital trade system. Keywords: dropshipping, commercial law, positive law, digital trade, consumer protection